2021
DOI: 10.1016/j.bbamem.2020.183511
|View full text |Cite
|
Sign up to set email alerts
|

Membrane nanodomains homeostasis during propofol anesthesia as function of dosage and temperature

Abstract: Some anesthetics bind and potentiate g-aminobutyric-acid-type receptors, but no universal mechanism for general anesthesia is known. Furthermore, often encountered complications such as anesthesia induced amnesia are not understood. General anesthetics are hydrophobic molecules easily dissolving into lipid bilayers. Recently, it was shown that general anesthetics perturb phase separation in vesicles extracted from fixed cells. Unclear is whether under physiological conditions general anesthetics induce perturb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Pain medication Paracetamol [283][284][285] Pain medication, opioid receptors Morphine [132], Fentanyl [132], Fentanyl and its analogues [286], Codeine [287] Local anesthetics Benzocaine [288][289][290], KP-23 [147], Dibucaine [291], Lidocaine [289,292,293], Articaine [289], Tetracaine [294,295], Prilocaine [296], Dyclonine, Butamben [290] General anesthetic Xenon [124,125], Chloroform [292,[297][298][299][300][301], Halothane [146,298,302,303], Isoflurane [297,299,304,305], Phenyl-ethanol [306], Desflurane [305,307], Sevoflurane [305,308], Propofol [305,309,310], Diethyl ether [298,308], Enflurane…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain medication Paracetamol [283][284][285] Pain medication, opioid receptors Morphine [132], Fentanyl [132], Fentanyl and its analogues [286], Codeine [287] Local anesthetics Benzocaine [288][289][290], KP-23 [147], Dibucaine [291], Lidocaine [289,292,293], Articaine [289], Tetracaine [294,295], Prilocaine [296], Dyclonine, Butamben [290] General anesthetic Xenon [124,125], Chloroform [292,[297][298][299][300][301], Halothane [146,298,302,303], Isoflurane [297,299,304,305], Phenyl-ethanol [306], Desflurane [305,307], Sevoflurane [305,308], Propofol [305,309,310], Diethyl ether [298,308], Enflurane…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Recent studies performed using multiple experimental techniques (Super-Resolution Microscopy dSTORM, Patch-Clamp, Fluorescence Resonance Energy Transfer) have demonstrated that both chloroform and isoflurane disrupt lipid domains (rafts) that contain the ganglioside GM1 [299]. Another anesthetic, propofol, at concentrations in the range 1 µM to 5 µM, has also been found to destabilize nanodomains in cellular membranes via Binned Imaging Fluorescence Correlation Spectroscopy [309]. Thus, the significant perturbations of the structure of bilayers in the liquid ordered phase, observed in MD simulation studies [271,308], are in agreement with experimental observations.…”
Section: Drug Membrane Interaction Can Play a Role In The Mechanism Of Drug Action-case Of Anestheticsmentioning
confidence: 99%
“…Observing the effect of drug on the patient, the variation of BIS values may depend on the effective Ce, drug concentration by the experimental non-linear Eq. (5) [6][7][8], named the Hill-Curve in the PD model. In the Hill equation, Ce (t) is the concentration of propofol (μg/ml) in the brain.…”
Section: Pk-pd Methodsmentioning
confidence: 99%
“…A current review of pharmacokinetics and pharmacodynamics approaches to optimize the anesthetic drug administration was performed [3,4]. In this pursuit, advanced mathematical techniques can be of superb value, for instance, robust PID control [5], fuzzy-type I/II [6,7], propofol injection robot-assistant [8,9] and target control infusion [10]. Some of the auto-drug delivery systems have widely used bispectral index monitoring [11,12], as variables of control modeling to administer the propofol dose during the anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that benzyl alcohol (BA), a routinely used anesthetic, hyperfluidizes the membrane and induces the reorganization of domains 46 . A recent work showed that propofol also reorganizes cholesterol-dependent domains in cell membranes 47 .…”
Section: Heptanol Induces Hyperfluidization and Domain Segregation In Model And Live Cell Membranesmentioning
confidence: 99%